PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Kadek Denis Hery Widani; Gde Bayu Surya Parwita; Ni Yoman Suryani (STIMI Handayani Denpasar, 2018)
This study aims to determine the effect of transformational leadership andjob satisfaction on employee performance at CV AGUNG PAPER Klungkung-Bali.The number of samples in this study were 38 employees. This research uses saturatedsampling technique. Methods of data collection using observation methods, interviewsand questionnaires. Methods of data analysis using multiple linear analysis. Theresult shows that partially transformational leadership (X1) has negative effect notsignificant to performance variable (Y) with t significance = -0,590 and ttable =1,68957. So -0.590 <1.68597. job satisfaction (X2) has a significant positive effectwith significance that is tcount = 3.852 and ttable = 1.68957 Thus 3.852> 1.65993.Simultaneously Variable transformational leadership (X1) and job satisfaction (X2)have an effect on employee performance (Y) with significance that is Fcount = 8,565and Ftabel = 3,27. So 8,565> 3.09. So this research is expected to give input inchoosing the leadership style used in leading company in CV AGUNG PAPER andthe management is expected to pay more attention to job satisfaction of employeesto improve performance.